Osama and The Entry of Al Qaeda to Southeast Asia in Historical Perspective: A Preliminary Note - Herdi Sahrasad; Yanuardi Syukur; Al Chaidar; Dedy Tabrany; Muhammad Ridwan (Budapest International Research and Critics University, 2019)
Southeast Asia captivates Al Qaeda (Saudi Arabia/Middle East) to enter this region because Osama Bin Laden knows that Southeast Asia is the second priority of the US in fighting international terrorism. Southeast Asia is also referred to as